Bioactive Indanes: Proof of Concept Study for Enantioselective Synthetic Routes to PH46A, a New Potential Anti-Inflammatory Agent - Tao Zhang (Molecules, 2018)
PH46A is a single enantiomer and a member of the 1,2-indane dimer family. It has two contiguous stereogenic centers with S,S configurations, one of which being a quaternary center, which has been developed as a clinical candidate for the treatment of inflammatory and autoimmune conditions. The current synthetic route to PH46A involves the generation of an unwanted enantiomer (R,R)-7, thus reducing the final yield significantly. Therefore, we have investigated potential alternatives to improve the efficiency of this synthesis. The first phase of the study has demonstrated proof of principle for a chiral alkylation of ketone 3 using phase-transfer catalysis, providing a key intermediate ketone (S)-4. The parent alkaloids required for the synthesis of PH46A, quinine or cinchonidine, have also been identified. Promising enantiomeric excesses of up to 50% have been achieved to date, and the use of an alternative substrate, unsaturated ketone 9, has also opened up further avenues for optimisation in future studies. The second part of the study involved preliminary screening the effects of a panel of hydrolase enzymes on (rac)-4 in order to identify a potential chemo-enzymatic route to optimise the introduction of chirality into PH46A at early stage of the synthesis. The hydrolase module has also yielded positive results; enzyme AH-46 with MtBE providing a selectivity factor of 8.4 with enantiomeric excess of 77%. Overall, positive results were obtained in this proof of concept study described herein. It is believed that conditions of both chiral PTC alkylation and biocatalytic hydrolysis could be optimised to further enhance the selectivity and improve the overall yield. This work is currently ongoing.